Pre- and post-spawning condition descriptors for the Indian major carp, Cirrhinus mrigala - TIBILE, RAJU M; GHODE, GAJANAN S (The Indian Journal of Animal Sciences, 2022)
Mrigal or Cirrhinus mrigala (Hamilton 1822) is one of the important aquaculture species in India. During 2017, mrigal contributed 5.7% to the aquaculture production of India. The present study was undertaken to describe the hatchery-level pre- and post-spawning condition, i.e. weight changes in the length-weight relationships (LWRs) and the weight-weight relationships (WWRs) associated with the two phases for the mrigal males and females used as broodstock from a commercial IMC hatchery. For the 18 pairs of individuals sampled, the TL (total length) ranged from 42–55 cm and 39–54 cm, and the BW (body weight) from 0.83–1.46 kg and 0.52–1.35 kg respectively for males and females. The GSI was recorded at 10.5% for males and 20.4% for females. The pre- and post-pawning weights differed significantly in both sexes based on paired t-test. Trends in the LWR and weight-weight slopes have been discussed in the article.